Computerisation of the University of Malaya Library (UML): issues of implementation - Teh, K.H. (Perpustakaan Universiti Malaya, 1991)
The Library started implementing its computerized integrated library project in January 1991. The complete computerization of the Library is envisaged to take place in 2 phases. Phase I encompasses the installation and operation of the VAXcomputer and the ATLAS integrated library software. A total of 100 terminals distributed within the Library system will be connected to the main computer system in a campus-wide network. Phase /I will involve some upgrading to the hardware configuration in terms of memory, disk storage, and other encitterv equipment to accomodate up to 300 concurrent users to the system. This includes the additional terminals for the branch libraries as well as the links from users in the various faculties, departments to the library network. Phase I which is currently in progress is being implemented on a turnkey basis, and is scheduled for completion by the end of 1991. The first three months have been scheduled for site preparation and delivery of the computer hardware, followed by three months of application software installation, training, testing and acceptance of the system. The system will be monitored in actual operation for the next 6 months till the end of 1991. Work has been going on according to schedule, save for an anticipated delay in the outdoor cabling work due to a shortage of the required cable. Implementation of the ATLAS software will focus on getting some modules to become operational as early as possible, to allow library users in general to enjoy tangible benefits from the computerization project. Problems in implementing a big project like this is inevitable, but to date all have been speedily resolved with the vendor.